KAJIAN PSIKOANALISIS DALAM NOVEL PRIA TERAKHIR KARYA GUSNALDI - Misra Nofrita; M Hendri (STKIP ROKANIA, 2017)
The purpose of this study is to describe: (1) The main aspects of the characters' personalities id; (2) the personality of the main character from the aspect ofego; (3) the personality of the main character from the aspect of the superego. This study is a qualitative study using descriptive methods. Aspects id seen when People prefer the feeling that likes the same sex and no desire of leaders to resist such measures so that aspect is very influential id. Aspects of the ego is not overstated by the main character in this novel aspects of the ego and superego are not raised so that the main character emphasizes the feelings, no desire to escape the kind of relationship does.